Corporate Investment in Abstract Art – A Market Study - Anjali Thapa (International Journal of Control and Automation, 2019)
In this article, we will apply the idea of a systemic approach to the art market and identify the potential dangers associated with artworks. Considering the topic of returns, the author separates the economic and aesthetic returns on art. In addition, the methods for calculating the economic returns on art have been examined. The many forms of financial risk that might occur while purchasing artwork are examined in detail. Investments in works of art often have poor liquidity since it is very difficult to convert the asset into cash. Investments with a third party often have more liquidity. In contrast to the shorter time horizon of indirect investments, such as those in stocks, direct investments in works of art should be seen as long-term investments. In contrast to other types of direct investments, those in works of art do not guarantee a steady return. Investments in artworks, although not directly yielding interest like investments in stocks and bonds, may nonetheless be stable (e.g. dividends). Particularly securities investments and indirect investment in works of art seem to be characterised by financial motives. The importance of non-monetary objectives decreases.